Mind the gap: Institutional and individual antecedents of entrepreneurial trajectories in the academic context - Teita Bijedić; Simone Chlosta; Sebastian Nielen; Arndt Werner (Institut für Mittelstandsforschung (IfM) Bonn, 2017)
This study analyses institutional, job-related, and individual antecedents of entrepreneurial activi-ties from a longitudinal perspective. We take a holistic look at the start-up process incorporating entrepreneurial gestation activities (nascent entrepreneurship) and finally business creation (entre-preneurship) by combining two waves of a survey with a time interval of three years. Focusing on researchers reporting an entrepreneurial intention in wave one we found for example that pull factors as motivation to start a business reduce the probability to give up the business idea. Furthermore having generated an invention prevents researchers with a business idea from becoming a so-called "quitter" and pushes them towards starting their own business.
Keywords: L20; L26; 330; Academic Entrepreneurship; Nascent Entrepreneurship; Institutions